FILOSOFI RUMAH LONTIOK KHAS DESA WISATA PULAU BELIMBING DALAM KAJIAN ETNOSAINS - Ria Monica; Arbi, Hanafi; Endra Juni Harja; Elmustian; Fakhruddin Z (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Lontiok House is a traditional house of the Malay community in Kampar Regency, Riau, rich in philosophical values, distinctive boat-shaped architecture, and local wisdom. However, modernization and the scarcity of natural materials threaten the preservation of this traditional house, causing the younger generation to lose touch with their cultural roots. This study aims to explore the philosophical meanings and socio-cultural values of the Lontiok House, and to integrate this local knowledge through an ethnoscience approach so it can be scientifically explained. This study employed a descriptive qualitative method with a field study approach. Data were collected through direct observation in Pulau Belimbing Village, Kuok District, in-depth interviews with customary leaders/caretakers, and documentation. The results show that the Lontiok House reflects a strong harmony between humans, nature, and Islamic values. The curved roof characteristic (lontiok) symbolizes reverence to God, while the stilt structure represents an environmental adaptation to floods and microclimates (ethnoscience perspective).